Maturidade da Indústria 4.0: estudo de caso de um fabricante de televisores no Polo Industrial de Manaus - Paz Netto, Antonio da Silva (Brasil, 2024)
The objective of this article is to present the analysis of the level of maturity of industry 4.0 in the processes of a television manufacturer established in the Industrial Pole of Manaus, in two specific dimensions: supply chain and strategy and organization. The research was conducted through a quantitative case study, based on data collected from pimm4.0. Regarding the method, key participants of the company responded to the questionnaire that underpins the PIMM4.0 analyses. The results show a low level of industry 4.0 implementation, considering only the analyzed dimensions